Self-assessment as a self-regulated learning approach in English oral presentations: College students’ choices and perceptions - Benraghda, Abdelmadjid; Noor Raha, Mohd Radzuan; Lardhi, Fatima Ali Salah (Taylor and Francis Ltd, 2022)
Recently, alternative assessment (AA) has gained huge attention in oral ‎communication studies. An area that has progressively received momentous concerns in ‎the EFL/ESL literature is the employment of the self-assessment method. Despite this concern, ‎the empirical data on the college of engineering students’ willingness to implement self-assessment, their ‎perceptions towards it, and the impact of factors on their attitudes remain scant. Therefore, in ‎an attempt to contribute to this research-based, this study tries to investigate the engineering students’ perceptions towards self-assessments on developing their ‎oral presentation skills in an engineering scope. To accomplish this aim, the study recruited ‎‎110 participants. The study delved into the engineering students’ perceptions of ‎self-assessment strategy in two stages (pre-and post-questionnaire) in performing technical oral ‎presentations. A questionnaire was distributed to the students before and after ‎implementing the assessment. The findings revealed that the students possessed positive perceptions pertaining to self-assessment in both ‎stages, pre-and post-self-assessment.